Business ethics : a stakeholder and issues management approach - Weiss, Joseph W. (Mason, OH : Thomson South-Western, 2006)
This text examines the role of ethics in the business world and the ethical dilemmas encountered by managers. Ethical decisions do not take place in a vacuum, and many people, faced with their own interests and standards, are involved in business encounters every day. "Stakeholder and Issues Management" is this text's unique approach to teaching business ethics. It pays special attention to the relationships among the many and varied stakeholders that have roles in business situations, including both the market and non-market entities that affect a business. Ethical issues must be addressed by individuals, groups, corporations, and even nations in very different ways, and the consequences differ with each person or group involved. This text gives students practical tools to handle moral dilemmas in the workplace and the world. Topics include risk management, preferential hiring, corporate legitimacy, and moral accountability.
1. Business Ethics, the Changing Environment, and StakeholderManagement -- Case 1-A. Enron -- Case 1-B. Microsoft. -- 2. Stakeholder and Issues Management Approaches. -- Case 2-A. Tylenol. -- Case 2-B. Adelphia. -- Case 2-C. WorldCom. -- Case 2-D. Arthur Andersen. -- 3. Ethical Principles, Quick Tests, and Decision-Making Guidelines. -- Case 3-A. Sam Waksal and Imclone. -- Case 3-B. AaronFeuerstein and Malden Mills. -- Case 3-C. Ford Pinto Crisis. -- 4. TheCorporation and External Stakeholders: Managing MoralResponsibility in the Marketplace. -- Case 5-A. Global Most AdmiredCompanies (Fortune.com). -- Case 5-B. High-Tech PR Firm. -- 5. TheCorporation and Internal Stakeholders: Value-Based Moral Dimensionsof Leadership, Strategy, Structure, Culture, and Self-Regulation.-- Case 4-A. Nike. -- Case 4-B. Napster. -- Case 4-C. Dow Corning. -- Case4-D. Gun Control. -- 6. Employee Stakeholders and the Corporation.-- Case 6-A. Sharon Watkins - Enron Whistle-Blower. -- 7. The GlobalEnvironment, Stakeholder Management, and MultinationalCorporations. -- Case 7-A. -- Wal-Mart. 8. Business Ethics in theTwenty-First Century.
Includes bibliographical references and index.
1
Keywords: Business ethics; Business ethics; Social responsibility of business